Potential of rainwater harvesting in a thirsty world: A survey of ancient and traditional rainwater harvesting applications - Ferrand, Ezgi Akpinar; Cecunjanin, Fatima (Geography Compass, 2014)
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-046-559-732-638 tex.type: [object Object]
Keywords: dept.egm; peer-reviewed

Use of aguadas as water management sources in two southern maya lowland sites - Ferrand, Ezgi Akpinar; Dunning, Nicholas P; Lentz, David L; Jones, John G (Ancient Mesoamerica, 2012)
Aguadas, either natural or human-made ponds, were significant sources of water for the ancient Maya. Aguadas are common features in the Maya Lowlands and make valuable locations for collecting archaeological and paleoenvironmental data. This article discusses research conducted at four aguadas around two adjacent Maya sites, San Bartolo and Xultun in Peten, Guatemala. Both San Bartolo and Xultun were established during the Preclassic period. However, the fates of the two sites differed, as Xultun continued to prosper while the city of San Bartolo was abandoned near the close of the Late Preclassic period. We argue that aguadas provide important clues for understanding the fate of these two ancient communities and many others in the Maya Lowlands. Copyright © 2012 Cambridge University Press.
35 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-122-134-377-577 tex.type: [object Object]
Keywords: Guatemala [Central America]; Maya Lowlands; Peten; San Bartolo; archaeological evidence; dept.egm; paleoenvironment; planning history; urban planning; water management; water resource; water use

Observations of the Influence of Regional Beach Dynamics on the Impacts of Storm Waves on the Connecticut Coast During Hurricanes Irene and Sandy - Tait, James F.; Ferrand, Ezgi Akpinar (Learning from the Impacts of Superstorm Sandy, 2015)
The Connecticut shoreline is one of the most intensively developed in the country. In many locations, development has relied on the buffering capacity of broad beaches for protection against storms. Much of this development is at risk due to an insufficient understanding of regional beach dynamics. The coast is commonly regarded as “protected” by the presence of Long Island. Nonetheless, Irene and Sandy imposed significant property losses on coastal cities. The most severe damages were due to wave impact in areas with narrow beaches. Small differences (as little as 21 m) in beach width proved to be significant during these storms. Sheltering by Long Island does not prevent coastal erosion during local storms. In the long run, it does prevent the rebuilding of the beach during fair weather by limiting the energy available for shoreward transport. This dynamic makes the beaches naturally erosive and their buffering capacity transient at best.
Keywords: Beach erosion; Beaches; Buffering capacities; Coastal cities; Coastal erosion; Connecticut beach dynamics; Dynamics; Energy asymmetry; Erosion; Fair weather; Hurricane Irene; Hurricane Sandy; Hurricanes; Property loss; Storm wave impacts; Storm waves; Storms; Water waves; beach erosion; dept.egm; energy asymmetry; faculty_collection; storm wave impacts

Rainwater Harvesting as an Effective Climate Change Adaptation Strategy in Rural and Urban Settings - Ferrand, Ezgi Akpinar (Managing Water Resources under Climate Uncertainty: Examples from Asia, Europe, Latin America, and Australia, 2015)
Human societies are known for their resilience and ability to adapt to short- and long-term environmental change. Despite their pragmatism and adaptability, humans could be forced to move and/or seek better conditions for survival, especially when climate change and water availability are at issue. This chapter provides case studies on easy-to-adopt rainwater harvesting applications as effective climate change adaptation strategies in rural and urban settings to increase human resiliency.
Citation Key Alias: lens.org/158-085-691-782-246
Keywords: Climate Change Adaptation; Climate change adaptation; Rainwater Harvesting; Rainwater harvesting; Urban and Rural Settings; Urban and rural settings; dept.egm